COMPARISON OF PERITONEAL CLOSURE VERSUS NON-CLOSURE DURING CAESAREAN SECTION - Takreem, Amera (Journal of Ayub Medical College Abbottabad, 2015)
Background: In modern obstetrics caesarean sections are commonly used and in all caesarean sections either peritoneal closure is done or not. This cases series was conducted to record outcomes in our setup. Methods: Cases of caesarean sections were followed for adhesions and non-adhesions in peritoneal closure and non-closure cases from 1st January to December 2011 at DHQ Hospital Haripur. In non-peritoneal closure cases adhesions were marked as compare to non-adhesions in peritoneal closure cases. Results: Sixty-five cases of peritoneal closure and 30 cases of non-peritoneal closure were followed up. There were more cases of adhesions in non-closure group (p<0.05). Conclusion: Peritoneal closure is beneficial in routine caesarean sections. Keywords: Adhesions, Caesarean sections, peritoneal closure, peritoneal non closure